Nutritional Profile of Some Tropical Fruits in Bangladesh: Specially Anti-Oxidant Vitamins and Minerals - Jahan, S; Gosh, T; Begum, M; Saha, BK (Bangladesh Journal of Medical Science, 2011)
Objective: Fruits and vegetables are important for the daily diet as these contain micronutrients, fiber, potassium, folate, Vitamin C, vegetable proteins, carotenoids and polyphenols, which act as antioxidants within the body as well as bio-functional components. The aim of the study is to establish nutritional profile specially antioxidant vitamins and minerals of tropical fruits in Bangladesh. Methodology: Nutritional composition and physico-chemical properties, such as pH, titratable acidity, moisture, total soluble solid, crude fibre, total carbohydrate, total protein, total fat, total energy, vitamin C, beta-carotene, ash, sodium, potassium, iron, zinc, copper, manganese, phosphorus, calcium and magnesium content of ten tropical fruits namely Blackberry, Java apple, Jack fruit, Pineapple, Carambola (Star fruit), Golden apple, Mango, Melon, Monkey jack, Star gooseberry were determined according to standard methods. Results: Results of this study suggest that the tropical fruits of Bangladesh were excellent source of antioxidant vitamins and minerals like vitamin C, beta- carotene, iron, zinc, copper and manganese. These fruits were also good source of potassium, phosphorus, calcium and magnesium but poor source of protein and fat and sodium. Conclusion: Present study strongly suggests that star gooseberry, monkey jack, pineapple and golden apple were antioxidant vitamins and minerals enriched tropical fruits. Key words: Antioxidant vitamins and minerals; micronutrients; tropical fruits. DOI: http://dx.doi.org/10.3329/bjms.v10i2.7804 Bangladesh Journal of Medical Science Vol.10 No.2 Apr’11 pp.95-103